2018
DOI: 10.5604/01.3001.0012.4712
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fine Needle Aspiration Cytology of Thyroid Gland with Histopathological Results

Abstract: Fine needle aspiration cytology (FNAC) is considered as the gold standard diagnostic test for the diagnosis of thyroid nodules. It is a cost-effective procedure that provides specific diagnosis rapidly with minimal complications. It plays an important role in the determination of treatment- patients with suspected malignancy diagnosis can be subjected to surgery. On the other hand it can decrease the rate of unnecessary surgeries. Aims: The aim of this study was to evaluate and compare the correlation, accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 0 publications
7
26
1
7
Order By: Relevance
“…As expected, our series were predominantly female (female to male; 4:1) with a comparable mean of age, which is in keeping with other studies [ 12 ]. Moreover, other parameters, including (BMI, Vit D, pre-op TSH, anti-thyroglobulin antibody, and anti-thyroid peroxidase antibody) showed almost no significant differences between both genders' groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, our series were predominantly female (female to male; 4:1) with a comparable mean of age, which is in keeping with other studies [ 12 ]. Moreover, other parameters, including (BMI, Vit D, pre-op TSH, anti-thyroglobulin antibody, and anti-thyroid peroxidase antibody) showed almost no significant differences between both genders' groups.…”
Section: Discussionsupporting
confidence: 92%
“…The diagnostic accuracy of FNA to detect malignancy for thyroid lesions is 85.88%. Other studies reported 83.6% [29] to 89.46% [12] accuracy of FNA, which supports ours.…”
Section: Discussionsupporting
confidence: 91%
“…In the study of Chieng J et al, FNAC predicted malignancy with a sensitivity, speci city, PPV, NPV, false positive rate, false negative rate and total accuracy of 90.7%, 53.6%, 43.3%, 93.7%, 46.4%, 9.3% and 64.1%, respectively [37]. However, FNAC is considered to be "uninterpretable" in 10 to 20% of cases or simply "suspicious" in 9 to 38% of cases [38].In addition, it is currently estimated that cytologically indeterminate results are diagnosed in up to 25% to 30% of thyroid biopsies [39,40].Therefore, the use of molecular markers is important for improving diagnostic accuracy. In this study, blood E2F3 mRNA predicted malignancy with a sensitivity, speci city, PPV, NPV, and accuracy of 90%, 60.9%, 70.5%, 85.47%, and 74.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Those changes led a significant decrease in surgery rates when compared with the period before TBSRTC without any decrease in malignancy rates 5 . The benefit of TBSRTC has been represented by several studies and metaanalyses [6][7][8][9] . However, TBSRTC alone may fail in decision making particularly in intermediate (III, IV and V) categories and adjunct diagnostic methods such as repeating FNAB, molecular testing and lobectomy have been recommended for more accurate diagnosis [10][11] .…”
Section: Introductionmentioning
confidence: 99%